Effect of Levilactobacillus brevis and Limosilactobacillus fermentum combined with carrot powder on the quality, safety, and microbial community of dry-fermented sausages - Siqi Zhang; Shimiao Wang; Xianhao Zhang; Hao Shang; Ying Yue; Bingrui Guo; Zhiping Zhao; Shengjie Li; Xinping Lin (Food Bioscience, 2026)

Genesis of the Jiawula Pb–Zn–Ag deposit in the Great Xing’an Range, NE China: constraints from fluid inclusions and S–Pb isotopes - Hongzhe Xie; Guiyuan Sun; Quzong Baima; Xinyu Gao; Ziwen Yang; Rui Tian; Lin Yang; Licheng Zhao; Zhiping Li (Journal of Asian Earth Sciences, 2026)

Settling by water: Human habitation adapted to landscape evolution at the Xuecheng site in the lower reaches of the Yangtze River during the Mid-late Holocene - Zhiping Zhang; Zhujun Hu; Xingyu Zhou; Hui Peng; Jue Sun; Jiahao Xu; Hongwei Shi; Lin Yang; Ping Zhang; Feng Xu; Harry F. Lee; Xin Jia (Science China Earth Sciences, 2026)

Unveiling the molecular diversity of toxins and non-toxins in the medicinal sea snake Hydrophis cyanocinctus through integrated venomics investigation - Jiayi Lin; Zhaoran Yu; Yue Cheng; Sheng Han; Ruiwei Ye; Dandan Yang; Xiawen Dang; Haorui Dai; Zhiping Zhao; Yonghong Zhou; Yiming Lu; An Li (Toxicon, 2026)

Stepwise enhanced photoelectrochemical activity of BiOCl by Fe(III)-doping and aptamer immobilization for ultrasensitive detection of tetracycline - Yifan Chen; Yuan Zhu; Yiyang Lin; Feng Gao; Zhiping Song; Xiaohui Dai; Jiancong Ni; Qingxiang Wang (Food Chemistry, 2026)

Chang’e-6 lander reveals local hour-scale temporal variations in lunar surface water - Honglei Lin; Heng-Ci Tian; Sheng Gou; Wei Yang; Jinning Li; Li Liu; Kai Fan; Sen Hu; Rui Xu; Zhiping He; Yong Wei; Yangting Lin (Science Bulletin, 2026)

The intensity of the late Holocene drought in northern China related to Arctic Sea ice - Jiaju Zhao; Qianwen Zhang; Zhongwei Shen; Zhiping Zhang; Jie Chen; Lin Chen; Jinzhao Liu; Yunning Cao; Jing Hu (Global and Planetary Change, 2026)

The short effect of ambient temperature on childhood asthma and wheezing: a combination of a nested case-control study and a case-crossover study - Jiatao Zhang; Shuoxin Bai; Shaoqian Lin; Yanling Wu; Fangyi Wang; Yuxiu Liang; Zhiping Wang (International Journal of Biometeorology, 2026)

Vegetation responses to the mid-Holocene abrupt climate events in the Forest-Steppe Ecotone in northern China - Yao Zhang; Lili Niu; Qiaoyu Cui; Yi Lin; Zhiping Zhang; Jiaju Zhao; Xinwei Yan; Aifeng Zhou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

AEG-1/MTDH Enhances Hepatocellular Carcinoma Radioresistance by Recruiting PTBP1 Via SND1 To Stabilize ATG5 mRNA and Promote Protective Autophagy - Xiaochun Chen; Yu Wang; Qishuai Guo; Xing Lin; Zhiping Yuan; Wei Liu; Chuan Lin; Yongjun Li; Yongpeng He (Cell Biochemistry and Biophysics, 2026)

Modulating excited states of multiple resonance emitter via through-space conjugation toward pure-green electroluminescence - Xiaoxian Song; Junxuan Lin; Zhiqiang Li; Zhiping Yan; Xuming Zhuang; Hai Bi; Yue Wang (Chemical Engineering Journal, 2026)

Instant gel-forming microcapsules based on micronized-κ-carrageenan for bitter taste quenching bioinspired by the passion fruit seed - Jiao Song; Linjie Tian; Shuyu Deng; Yifei Zhang; Junzhi Lin; Zhiping Guo; Hongyan Ma; Dingkun Zhang; Li Han; Zhimin Ci (Carbohydrate Polymers, 2026)

Direct oxidation of trace methane to formaldehyde under ambient conditions by piezo-photocatalytic synergy - Qiyu Zhang; Li Rong; Yue Jiang; Zhiping Zhu; Xiaochang Lin; Yongzhen Ding; Hongmin Dong; Dezhao Liu (Chemical Engineering Journal, 2025)

Efficient NMR spectroscopy approach for the determination of the relative configuration of Δ5,6Δ11,12-jatrophane diterpenes and their chemotherapy sensitization activities - Wenjing Tian; Jie Li; Mi Zhou; Yanlan Yang; Yingting Lin; Guanghui Wang; Zhiping Zeng; Yuting Bian; Cuiling Sun; Rong Ding; Haifeng Chen (Phytochemistry, 2025)

Sedimentary Structure Characteristics and Spatial Distribution Pattern of the Zhaoji Salt Mine Derived from Dense Array Ambient Noise Tomography - Hongwei Wang; Xiaofeng Tian; Qiaoxia Liu; Jia Cheng; Ming Zhou; Zhiping Xu; Jiyan Lin; Shuaipeng Zhu (Journal of Earth Science, 2025)

Tree species classification via a two-stage deep learning framework: integration of enhanced spectral reconstruction with classifiers - Zhiping Lin; Yuhao Yuan; Qun Zang; Zhongmou Fan (International Journal of Remote Sensing, 2025)

Deciphering the venom components of Sea snakes: Integrating dual proteomic techniques to uncover the bioactive potential of Hydrophis curtus - Yingying Li; Haorui Dai; Zhiping Zhao; Ruiwei Ye; Sheng Han; Dandan Yang; Hanyu Pan; Jiayi Lin; Xiawen Dang; Yue Cheng; Zhaoran Yu; An Li; et al. (Toxicon, 2025)

A review of recent hybridized machine learning methodologies for time series forecasting on water-related variables - Van Kwan Zhi Koh; Ye Li; Xing Yong Kek; Ehsan Shafiee; Zhiping Lin; Bihan Wen (Journal of Hydrology, 2025)

Histopathological Insights into Demyelination and Remyelination After Spinal Cord Injury in Non-human Primates - Junhao Liu; Zucheng Huang; Kinon Chen; Rong Li; Zhiping Huang; Junyu Lin; Hui Jiang; Jie Liu; Qingan Zhu (Neuroscience Bulletin, 2025)

A new approach to color correction and equalization for generating mars global color image mosaics from Tianwen-1 MoRIC images - Xin Ren; Xiaoxia Zhang; Wangli Chen; Wei Yan; Xingguo Zeng; Xu Tan; Xingye Gao; Qiang Fu; Lin Guo; Qing Zhang; Zhaopeng Chen; Guobin Yu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Shrinkage and bending performance of trapezoidal wet joints in steel-UHPC composite decks - Han Xiao; Wei Wang; Chen Xu; Biao Ma; Zhiping Lin; Qingtian Su (Engineering Structures, 2025)

Seasonal responses of microbial communities to water quality variations and interaction of eutrophication risk in Gehu Lake - Qiqi Chen; Yuxia Liu; Meng Zhang; Kuangfei Lin; Zhiping Wang; Lili Liu (Science of The Total Environment, 2024)

Higher water content observed in smaller size fraction of Chang'e-5 lunar regolith samples - Honglei Lin; Rui Xu; Shuai Li; Rui Chang; Hejiu Hui; Yang Liu; Hengci Tian; Kai Fan; Zhiping He; Huaiyu He; Wei Yang; Yangting Lin; et al. (Science Bulletin, 2024)

Catalytic depolymerization of Camellia oleifera shell lignin to phenolic monomers: Insights into the effects of solvent, catalyst and atmosphere - Shukun Qiu; Xudong Liu; Yiying Wu; Yan Chao; Zhicheng Jiang; Yiping Luo; Baining Lin; Rukuan Liu; Zhihong Xiao; Changzhu Li; Zhiping Wu (Bioresource Technology, 2024)

Advantages of targeted ventilation for farrowing houses: An analysis from perspectives of thermal environment, biosecurity and ventilation efficacy - Longhuan Du; Xuan Tao; Lin Zhu; Jinchuan Li; Min Fu; Jingwen Lai; Chaowu Yang; Zhiping He (Computers and Electronics in Agriculture, 2024)

Tuning oxygen vacancies via photoinduced defect engineering in plasma pre-treated TiO2 for efficient solar-light-driven oxidation of trace methane - Qiyu Zhang; Jiakang Duan; Zhiping Zhu; Li Rong; Xiaochang Lin; Hongmin Dong; Dezhao Liu (Chemical Engineering Journal, 2024)

Hyper-Parameter Optimization-based multi-source fusion for remote sensing inversion of non-photosensitive water quality parameters - Yuhao Yuan; Zhiping Lin; Xinhao Jiang; Zhongmou Fan (International Journal of Remote Sensing, 2024)

A 76-m per pixel global color image dataset and map of Mars by Tianwen-1 - Jianjun Liu; Xin Ren; Wei Yan; Wangli Chen; Xingguo Zeng; Xiaoxia Zhang; Xu Tan; Xingye Gao; Qiang Fu; Dingxin Liu; Lin Guo; Qing Zhang; et al. (Science Bulletin, 2024)

Absence of a water depth signal in archaeal tetraether lipids from surface lake sediments in areas with intensive human activity: A case study from Daihai Lake, Inner Mongolia - Zhongwei Shen; Yanwu Duan; Zhiping Zhang; Jie Chen; Lin Chen; Aifeng Zhou; Jianbao Liu; Fahu Chen (Chemical Geology, 2024)

Abrupt cooling of cold seasons at the middle-late Holocene transition revealed by alkenone records from North China - Jiaju Zhao; Jianbao Liu; Jinzhao Liu; Shengqian Chen; Aifeng Zhou; Lin Chen; Zhiping Zhang; Zhongwei Shen; Jie Chen; Yunning Cao; Jing Hu; Qianwen Zhang (Quaternary Science Reviews, 2024)

Controllable lignin valorization to value-added aromatic chemicals by a UV-assisted ternary heterogeneous photo-fenton catalytic system - Fen Wang; Lin Zhang; Zhiping Wu; Wenbo Peng; Peng Zhan; Lishu Shao; Hui Wang; Yan Qing; Hanxue Lin; Quan Wei; Na Liu; Zhaohui Tong (Fuel, 2024)

Semisynthesis, anti-oomycete and anti-fungal activities of ursolic acid ester derivatives - Lina Zhu; Yuee Tian; Tiewei Wang; Xiaobo Huang; Lin Zhou; Liu Shengming; Genqiang Chen; Zhiping Che (Natural Product Research, 2024)

A quantitative model to estimate major oxide abundances on the Moon based on in situ reflectance spectral data of Chang'e missions - Zhenxing Zhao; Yazhou Yang; Xing Wu; Yang Liu; Feng Zhang; Rui Xu; Zhiping He; Yangting Lin; Yongliao Zou (Icarus, 2024)

Discovery and verification of bitter components in Panax notoginseng based on the integrated strategy of pharmacophore model, system separation and bitter tracing technology - Jing Yang; Min Qiu; Tai Lu; Shangdong Yang; Ji Yu; Junzhi Lin; Hongyan Ma; Zhiping Guo; Zhencai Chen; Xue Han; Dingkun Zhang (Food Chemistry, 2023)

Diverse relationship between the tropical night in South China and the water vapor transport over the South China Sea and the plausible causes - Ruidan Chen; Zhiping Wen; Wenting Lin; Yunting Qiao (Atmospheric Research, 2023)

Environmental-friendly biomass-based Janus ink/urushiol modified cotton fabric for efficient solar-driven interfacial evaporation - Weibin Bai; Xu Zhang; Ying Chen; Zhiping Lian; Shijing Zheng; Xinghang Chen; Yucai Lin; Rongkun Jian (Chemical Engineering Journal, 2023)

Recent Advances in Understanding Multi-scale Climate Variability of the Asian Monsoon - Wen Chen; Renhe Zhang; Renguang Wu; Zhiping Wen; Liantong Zhou; Lin Wang; Peng Hu; Tianjiao Ma; Jinling Piao; Lei Song; Zhibiao Wang; Juncong Li; et al. (Advances in Atmospheric Sciences, 2023)

A life course approach to asthma and wheezing among young children caused by ozone: A prospective birth cohort in northern China - Shuoxin Bai; Liangliang Cui; Shuang Du; Xiaodong Zhao; Shaoqian Lin; Xiwei Yang; Jiatao Zhang; Yuxiu Liang; Zhiping Wang (Environmental Research, 2023)

Tumor microenvironment-responsive nanosystem achieves reactive oxygen species self-cycling after photothermal induction to enhance efficacy of antitumor therapy - Yuting Peng; Lianghao Cheng; Chunyi Luo; Fuquan Xiong; Zhiping Wu; Lin Zhang; Peng Zhan; Lishu Shao; Weihua Luo (Chemical Engineering Journal, 2023)

An Empirical Study on Water-Induced Shear Weakening Behaviors of Rough-Walled Sandstone Joints - Guohua Zhang; Bowen Zhang; Junpeng Zou; Feng Xiong; Zhiping Lin; Zhanrong Zhang (Rock Mechanics and Rock Engineering, 2023)

Designing Protograph LDPC Codes for Differential Chaotic Bit-Interleaved Coded Modulation System for Underwater Acoustic Communications - Zhiping Xu; Qiwang Chen; Yang Li; Guofa Cai; Lixiong Lin; Jiachun Zheng; Yanglong Sun (Journal of Marine Science and Engineering, 2023)
Underwater acoustic (UWA) communications face many challenges, such as large multipath delay, severe fading and the time-varying distortions. Chaotic modulations have shown advantages in UWA communications, but the reliability of current chaotic modulations is still not guaranteed. In this paper, a short-length protograph low-density parity-check (P-LDPC) code design framework for the differential chaotic bit-interleaved coded modulation (DC-BICM) system for UWA communication is proposed. This design framework, considering the requirements of short codes in UWA communications, integrates the DC-BICM system, UWA channel and the differential evolutionary code searching algorithm. Through this design framework, the optimized short P-LDPC code can be obtained. Simulation results show that the DC-BICM system with the proposed P-LDPC code can obtain more than 0.48 dB coding gain and reduce 32.6%~69.5% of the average number of iterations compared with the counterparts. Moreover, the reconstructed underwater image with the proposed P-LDPC code is clearest with the highest peak-signal-noise ratio value when compared with counterparts.

Maternal apparent temperature during pregnancy on the risk of offspring asthma and wheezing: effect, critical window, and modifiers - Jiatao Zhang; Shuoxin Bai; Shaoqian Lin; Liangliang Cui; Xiaodong Zhao; Shuang Du; Zhiping Wang (Environmental Science and Pollution Research, 2023)

Optimization of bovine embryonic fibroblast feeder layer prepared by Mitomycin C - Fang Zhao; Jianning Yu; Qiang Ding; Kunlin Chen; Shuwen Xia; Yong Qian; Yundong Gao; Zhiping Lin; Huili Wang; Jifeng Zhong (Cell and Tissue Banking, 2023)

Evaluation of cold plasma for decontamination of molds and mycotoxins in rice grain - Jian Guo; Zhiping He; Chao Ma; Wanting Li; Jiaoyu Wang; Fucheng Lin; Xingquan Liu; Ling Li (Food Chemistry, 2023)

Coupling of the ecosystems in North China with the East Asian summer monsoon rainfall during the Holocene - Jiaju Zhao; Jianbao Liu; Jinzhao Liu; Shengqian Chen; Li Wang; Aifeng Zhou; Zhiping Zhang; Zhongwei Shen; Jie Chen; Lin Chen; Yunning Cao; Jing Hu; et al. (Quaternary Science Reviews, 2023)

Analysis of the Mechanism of Water Inrush Geohazards in Deep-Buried Tunnels under the Complex Geological Environment of Karst Cave-Fractured Zone - Weishe Zhang; Yuyong Jiao; Guohua Zhang; Xi Zhang; Guangzhao Ou; Zhiping Lin (Journal of Earth Science, 2022)

RsmA3 modulates RpoS through the RetS‐Gac‐Rsm signalling pathway in response to H 2 O 2 stress in the phytopathogen Pseudomonas syringae - Xun Yu; Cui Meng; Xiaocheng Tan; Yuwei Su; Zhiping Cao; Tzann‐Shun Hwang; Lin Li (Environmental Microbiology, 2022)
Reactive oxygen species are a fatal challenge to the plant pathogenic bacterium Pseudomonas syringae . In this study, we reveal that the global regulatory protein RsmA3 from the RetS‐Gac/Rsm signalling pathway modulates RpoS in the early‐log growth phase in the P . syringae wild‐type strain MB03, thereby regulating oxidative tolerance to H 2 O 2 and ultimately affecting pathogenicity to the host plant. Following increased H 2 O 2 by external addition or endogenous induction by menadione, the resistance of the mutant strain Δ retS to H 2 O 2 is significantly enhanced due to rapid increases in the transcription of Rsm‐related non‐coding small RNAs (nc sRNAs), a sigma factor RpoS, and H 2 O 2 ‐detoxifying enzymes. Moreover, the Δ retS mutant is significantly less pathogenic in cucumber leaves. Seven Rsm‐related nc sRNAs (namely, rsmZ , rsmY and rsmX 1–5 ) show functional redundancy in the RetS‐Gac‐Rsm signalling pathway. External addition of H 2 O 2 stimulates increases in the transcription of both rsmY and rsmZ . Thus, we propose a regulatory model of the RetS‐Gac‐Rsm signalling pathway in P . syringae MB03 for the regulation of H 2 O 2 tolerance and phytopathogenicity in the host plant.

Identification and mapping of genetic locus conferring resistance to multiple plant viruses in soybean - Dagang Wang; Shengnan Chen; Zhiping Huang; Jing Lin (Theoretical and Applied Genetics, 2022)

The effect and its critical window for ambient temperature and humidity in pregnancy on term low birth weight - Shuang Du; Shuoxin Bai; Xiaodong Zhao; Shaoqian Lin; Yifan Zhai; Zhaojun Wang; Zhiping Wang (Environmental Science and Pollution Research, 2022)

Large‐scale circulation features responsible for different types of extreme high temperatures with extreme coverage over South China - Wenting Lin; Ruidan Chen; Zhiping Wen; Wei Chen (International Journal of Climatology, 2022)
This study classifies the summer extreme high temperatures (EHT) over South China into Day‐EHT, Night‐EHT and Mixed‐EHT (corresponding to EHT with extreme coverage only in daytime, only at night and both in daytime and at night) and compares their associated circulation patterns. All types of EHT are associated with the intensification and expansion of western Pacific subtropical high (WPSH). Concurrently, anomalous subsidence occurs over South China, which reduces the cloud cover and favours daytime warming. However, different types of EHT feature different circulation configurations. Day‐EHT are influenced by the northwestward‐extending WPSH and tropical cyclones, manifesting an abnormal anticyclonic‐cyclonic pair. Anomalous northeasterly winds dominate over South China, which cause lower humidity and faster heat dissipation and thus the EHT disappear at night. Night‐EHT are related to the westward‐extending WPSH and intensified East Asian westerly trough, presenting a subtropical anticyclonic anomaly and a mid‐latitude cyclonic anomaly. Anomalous southwesterly and northerly flows meet around South China, favouring more water vapour convergence in situ. The above‐normal humidity results in smaller amplitude of cloud cover reduction and weaker daytime warming compared to Day‐EHT, but favours heat maintenance and Night‐EHT. Moreover, the mid‐high‐latitude wave train preceding Day‐EHT (Night‐EHT) lies more northward (southward) with the upstream high‐pressure anomaly occurring around the Ural Mountains (Caspian Sea). Mixed‐EHT combine the anomalies for Day‐EHT and Night‐EHT and weak humidity anomaly occurs over South China, thus the daytime EHT could persist until night albeit cools down slightly. These distinguished features indicate that different types of EHT should be considered separately for better forecast and projection of EHT.

The effects of anthropogenic greenhouse gases and aerosols on the inter-decadal change of the South China Sea summer monsoon in the late twentieth century - Zhongxi Lin; Buwen Dong; Zhiping Wen (Climate Dynamics, 2020)

Removal of aqueous fluoroquinolones with multi-functional activated carbon (MFAC) derived from recycled long-root Eichhornia crassipes: batch and column studies - Lili Liu; Xin Chen; Zhiping Wang; Sen Lin (Environmental Science and Pollution Research, 2019)

PTEN-mediated mitophagy and APE1 overexpression protects against cardiac hypoxia/reoxygenation injury - Wenshuai Tang; Deqing Lin; Mingxiang Chen; Zhiping Li; Weimin Zhang; Wenping Hu; Fuping Li (In Vitro Cellular & Developmental Biology - Animal, 2019)

Recent Progress in Studies of the Variabilities and Mechanisms of the East Asian Monsoon in a Changing Climate - Wen Chen; Lin Wang; Juan Feng; Zhiping Wen; Tiaojiao Ma; Xiuqun Yang; Chenghai Wang (Advances in Atmospheric Sciences, 2019)

Comparison of Inorganic and Organically Bound Trace Minerals on Tissue Mineral Deposition and Fecal Excretion in Broiler Breeders - Geng Wang; Lujie Liu; Zhongpei Wang; Xun Pei; Wenjing Tao; Zhiping Xiao; Bojing Liu; Minqi Wang; Gang Lin; Tuoying Ao (Biological Trace Element Research, 2019)

Long-term groundwater storage changes and land subsidence development in the North China Plain (1971–2015) - Huili Gong; Yun Pan; Longqun Zheng; Xiaojuan Li; Lin Zhu; Chong Zhang; Zhiyong Huang; Zhiping Li; Haigang Wang; Chaofan Zhou (Hydrogeology Journal, 2018)

Using network to enhance the insights on correlation and pollution assessment of co-occurring metals in marine sediments, the East China Sea - Lili Liu; Yupeng Wang; Sen Lin; Hong Li; Xin Chen; Zhiping Wang; Kuangfei Lin (Environmental Science and Pollution Research, 2018)

The impact of tropical intraseasonal oscillation on the summer rainfall increase over southern China around 1992/1993 - Jiabao Wang; Zhiping Wen; Renguang Wu; Ailan Lin (Climate Dynamics, 2017)

Effects of tropical cyclone activity on the boundary moisture budget over the eastern China monsoon region - Xiaobin Lin; Zhiping Wen; Wen Zhou; Renguang Wu; Ruidan Chen (Advances in Atmospheric Sciences, 2017)

Profile of Citrobacter freundii ST2, a Multi-acyl-homoserine Lactone Producer Associated with Marine Dinoflagellates - Xinqi Huang; Yan Gao; Zhiping Ma; Guanghui Lin; Zhonghua Cai; Jin Zhou (Current Microbiology, 2017)

Aerobic debromination of BDE-209 by Rhodococcus sp. coupled with zerovalent iron/activated carbon - Lili Liu; Yacong Zhang; Ruihong Liu; Zhiping Wang; Feng Xu; Yilun Chen; Kuangfei Lin (Environmental Science and Pollution Research, 2016)

Relative importance of tropical SST anomalies in maintaining the Western North Pacific anomalous anticyclone during El Niño to La Niña transition years - Zesheng Chen; Zhiping Wen; Renguang Wu; Xiaobin Lin; Jiabao Wang (Climate Dynamics, 2016)

Detection of spotted fever group Rickettsiae in ticks from Zhejiang Province, China - Jimin Sun; Junfen Lin; Zhenyu Gong; Yue Chang; Xiaodong Ye; Shiping Gu; Weilong Pang; Chengwei Wang; Xiaohua Zheng; Juan Hou; Feng Ling; Xuguang Shi; et al. (Experimental and Applied Acarology, 2015)

Rare allele of HvLox-1 associated with lipoxygenase activity in barley (Hordeum vulgare L.) - Ganggang Guo; Dawa Dondup; Xingmiao Yuan; Fanghong Gu; Deliang Wang; Fengchao Jia; Zhiping Lin; Michael Baum; Jing Zhang (Theoretical and Applied Genetics, 2014)

Determination of biogenic amines in traditional Chinese fermented foods by reversed-phase high-performance liquid chromatography (RP-HPLC) - Xiao Gong; Xiaoxi Wang; Ningli Qi; Jihua Li; Lijing Lin; Zhiping Han (Food Additives & Contaminants: Part A, 2014)